A corpus-assisted discourse study of Chinese university students' perceptions of sustainability - Huang, Ruihong (Frontiers in Psychology, 2023)
Education for sustainable development (ESD) in the higher education context is playing a critical role in advancing the cause of sustainable development. However, previous research on university students’ perceptions of sustainable development is limited. This study used a corpus-assisted ecolinguistic approach to investigate students’ perceptions of sustainability issues and responsible actors to address these issues. This quantitative and qualitative study is based on a corpus of 501 collaborative essays on sustainability written by approximately 2000 Chinese university students collected with their permission. The results show that the students had a comprehensive perception of the three dimensions of sustainable development. Environmental issues have received the most attention from students, followed by economic and social ones. With regard to perceived actors, students were inclined to view themselves as active participants in the cause of sustainable development rather than as observers. They called for coordinated action of all relevant parties such as the government, business sectors, institutions, and individuals. On the other hand, the author also noticed a tendency towards superficial green talk and anthropocentrism in students’ discourse. This study aims to contribute to sustainability education by integrating findings into English as a foreign language (EFL) classes. Implications for sustainability education in the context of higher education are also discussed.